Penyuluhan pertanian indonesia: isu privatisasi dan implikasinya - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
ABSTRACT: The organization, mandate, and practices of agricultural and rural extension systems are changing worldwide, and it is vital that each region keep pace with the latest developments. The challenges of introducing appropriate institutional measures must be accepted by each government in order to reform the national agricultural extension systems in response to the global changes, otherwise the extension systems will become obsolete. Diverse agricultural extension funding and delivery arrangements have been undertaken since the mid-1980s by governments worldwide in the name of "privatization". Privatization is used in the broadest sense of introducing or increasing private sector participation, which does not necessarily imply transfer of designated state-owned assets to the private sector. The arguments for privatization are based upon: more efficient delivery of service, lowered government expenditure. and higher quality of services. Privatization of agricultural extension system implies 0 a division of appropriate role between public sector and private sector. Cost and service sharing among extension service providers can be formed into some systems encompass contract, vouchers, competitive grant fund, subsidize, and commercial extension service. This paper aims to discuss about privatization issues and its implications on Indonesian agricultural extension system. Related parties and sectors on Indonesian agricultural extension system should pay more attention in order to reform the old system and to reconstruct it into a new system--client-oriented extension